Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/s22062158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Label Design and Country of Origin Information in Wines on Consumers’ Visual, Sensory, and Emotional Responses

Abstract: This study aimed to evaluate the influence of origin information on Pinot Noir wine labels using eye-tracking and its associations with purchase intent, and hedonic and subconscious emotional responses. Two studies were carried out on untrained university staff and students aged 20–60 years old. Study 1 was conducted to assess consumers’ (n = 55; 55% males, and 45% females) self-reported and subconscious responses towards four design labels (with and without New Zealand origin name/script or origin logo) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…The brand and information regarding the characteristics of wines/cellars and territories of origin-available on the label or obtained through advice from wine influencers (storytelling)-are the main elements taken into consideration by demanding consumers [8,12]. This has also been confirmed by recent studies, which show that the consumption of quality wines has increased in recent years among certain groups of consumers (with particular characteristics and lifestyles) [8,9].…”
Section: Advances and Gaps In The Existing Literature And The Study's...mentioning
confidence: 78%
See 2 more Smart Citations
“…The brand and information regarding the characteristics of wines/cellars and territories of origin-available on the label or obtained through advice from wine influencers (storytelling)-are the main elements taken into consideration by demanding consumers [8,12]. This has also been confirmed by recent studies, which show that the consumption of quality wines has increased in recent years among certain groups of consumers (with particular characteristics and lifestyles) [8,9].…”
Section: Advances and Gaps In The Existing Literature And The Study's...mentioning
confidence: 78%
“…Since 1965, the COE, also known as the "made-in image" or "nationality bias," has been considered a psychological effect describing how consumers' attitudes, perceptions, and purchasing decisions are influenced by a product's country of production. This can refer to where a company has its production base, to where a product is designed/developed, or to other forms of value creation linked to a specific country [12][13][14][15].…”
Section: Country Of Origin Effect and Italian Wine Classificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a similar methodology, Meyerding and Merz (2018) [ 85 ] found evidence that an organic label positively affected consumers’ trust in food products. Furthermore, by employing eye-tracking and AFEA, Liu et al (2022) [ 86 ] evaluated the influence of origin information on Pinot Noir wine labels on consumers’ purchase intention. It was found that the country-of-origin (COO) information attracted consumers’ attention and that the COO drew more attention if presented as a logo rather than as in script or textual form.…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…Furthermore, a computer vision method was presented using a conventional RGB camera coupled with machine learning modelling to predict the type of rice based on morphocolorimetric parameters obtained through the images [7]. On the other hand, two papers focused on the use of non-invasive biometrics (i) to assess self-reported responses as well as eye tracking and emotional responses towards specific regions of interest (ROI) in packaging and labels using contactless biometrics through the BioSensory© application (The University of Melbourne, Parkville, VIC, Australia) [8], and (ii) to evaluate the influence of label design and country of origin in wine labels on consumers conscious and subconscious responses using contactless biometrics also with the BioSensory© application [9]. Spectral analysis in foods and beverages is one of the most used methods to assess their chemical fingerprinting.…”
mentioning
confidence: 99%